Obligatory role of ASK1 in the apoptotic surge of K(+) currents - Aras, Mandar A. (2005)
Apoptosis signal-regulating kinase 1 (ASK1) is a critical component of mitogen-activated protein kinase signaling pathways leading to cell death in response to cytokines and cellular stress. We use a dominant-negative (DN) form of ASK1 to show that this enzyme is necessary for the delayed surge in neuronal K(+) channel activity, a required step in apoptosis. Furthermore, expression of ASK1 DN also suppresses the apoptotic increase in Kv2.1 currents transiently expressed in Chinese hamster ovary cells. Finally, over-expression of thioredoxin, an inhibitory binding partner of ASK1, is sufficient to halt the apoptotic current surge in neurons. Thus, ASK1 is an obligatory component of the pro-apoptotic modulation of K(+) channels.